An evaluation of Payton v. New York - Campell, Carla (American journal of criminal justice, 1982)
The Supreme Court decision in Payton v. New York (1980) is evaluated. In this cose, the. Court remanded to the trial level tribunal a case in which an arrest was made and evidence was seized without a warrant. The author discusses the case thoroughly and compares the decision to other cases which dealt with the warrantless arrest and seizure of evidence. The author questions if the Court is becoming “too technical” in its interpretation of the 4th Amendment and poses once again the perennial question; “Where is the line drawn between protecting the nights of society from criminals and protecting the rights of criminals from judicial interpretation?”